ANALISIS PUEBI PADA WARTA JEMAAT GEREJA GMIT DI KOTA KUPANG PERIODE FEBRUARI – MARET 2024 - Nurhuda, Aris; Makan Malay, Narantoputrayadi; Nitbani, Semuel H.; Djokaho, Margaret P. E.; Leda, Anastasia J. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This research aims to investigate important aspects related to the use of PUEBI in the GMIT Congregation Newsletter in Kupang City. This goal is broken down into specific objectives, as follows. a) identify and describe the use of prepositions in the news of the GMIT church congregation in Kupang City; b) identify and describe the use of punctuation in the GMIT church congregation's newsletter in Kupang City; c) identify and describe the use of capital letters and bold letters in Indonesian by the GMIT church congregation in Kupang City. A worthy contribution from the results of this research is in the field of language and literature education, especially on linguistic issues. Many people don't pay attention to the correct Indonesian language rules. Through this research activity, we can contribute to the understanding of the good and correct use of Indonesian to the language community in general and especially to the news of the GMIT church congregation in Kupang City. Therefore, starting from this research activity, it can also contribute to students providing education and understanding of the use of PUEBI so that it can be synergized in writing courses.